Perbaikan Toleransi Ukuran Diameter Inti Produk Shoulder Clamp Dengan Mempertimbangkan Kapabilitas Proses Pengecoran - J. M. Tupan (ARIKA, 2012)
The design tolerance as one of the characteristics of quality is a critical stage in the design process and product. Reflects the absence of economies of size tolerance manufacturing process. Performance of the production process can be measured by indices of process capability. This study aims to redesign the new specification limits (tolerance) diameter core (core) products based on the ability of the clamp Shoulder-owned company, Tolerance and Tolerance Standard Casting. The analysis show that the casting process is currently capable of producing the products according to specifications defined by the index Cp = 0.65; Cpk = 0.50; CR = 1.55 and Cpm = 0:59. Based on the performance of the casting process is proposed an alternative six shoulder clamp diameter tolerance are 23:50 +- 0.80 mm, 0.82 mm +- 23:50, 23:50 +- 23:50 +- 1:20 mm 1:26 mm, 1.70 mm +- 23:50 and 23:50 +- 2:40 mm